Local inclusiveness in culture based economy in the development of ECER, Malaysia : case study from Kelantan. - Fatimah Yusof; Ishak Che Abdullah; Faizul Abdullah; Hazlina Hamdan (2013)
The production of culture in economic and urban landscape has received much attention within geography realm. There are many cultures that became a symbol of tradition to the community. The contribution of culture such as art, food, craft, textile and fashion can be preserved as a source of inspiration to produce new innovative products, added value and competitive advantage for a region. On the other hand, cultural economic geography is also about how people and their culture interact with their environments. Thus, this paper intends to investigate the level of local inclusiveness in culture based economy in the development region.